Biochemical and cytogenetic consequences of settleable atmospheric particulate matter on Pacific white shrimp Litopenaeus vannamei - Copetti, F. [UNESP]; Nobre, C. R.; Paço, M. S.; de Camargo, T. F.T.; Moreno, B. B.; Fernandes, M. N.; Schveitzer, R.; Pereira, C. D.S. (Elsevier, 2025)
This study hypothesizes that micro and nanoparticles of metals from metallurgical atmospheric emissions can trigger sublethal effects on the Pacific white shrimp Litopenaeus vannamei. We aimed to analyze cytotoxicity (Lysosomal Membrane Stability - LMS), Lipid peroxidation (LPO), genotoxicity (DNA strand break), and neurotoxicity (Acetylcholinesterase activity AChE) in shrimp exposed to environmentally relevant concentrations (0.001, 0.1, and 1.0 g.L−1) of settleable atmospheric particulate matter (SePM) for different times (T2, T4, T7, T15 and T30 days), and in several tissues (gills, hemolymph, muscle,e and hepatopancreas). LPO within the first 2 day, and LMS showed significant differences. From the seventh to the fifteenth day of exposure, the concentration of 0.1 g.L−1 exhibited significant effects. In the most extended exposure period (30 days), all concentrations triggered cytotoxicity effects on the Pacific white shrimp Litopenaeus vannamei. Thus, exposure to SePM can impair essential cellular functions, denoting a pre-pathological status. These findings underscore the potential hazards of metallurgical SePM to estuarine and farmed shrimp populations, emphasizing the need for ongoing monitoring and effective mitigation strategies to ensure aquaculture sustainability.
Keywords: Metallic particles; Shrimp; Sublethal effects; Toxicological potential; Tropical estuaries